Clustering Micromobility Devices based on Speed and Comfort - Amir Hassanpour; Alex Bigazzi (Findings)
Pedestrians and micromobility devices are grouped into 4 clusters with increasing speed and decreasing comfort. The Clusters are assigned a Path User Comfort Equivalent (PUCE) factor which can be used in pathway design to adjust volume impacts on pedestrian comfort. Clusters 1 (including skates and mobility aids), 2 (non-motorized cycles), 3 (most motorized devices), and 4 (moped-style scooters) have PUCE of 1.0, 2.1, 2.8, and 4.0 respectively. Scenario analysis shows that most pedestrians would still feel comfortable with a large shift from Cluster 2 to Cluster 3 (i.e., bicycle electrification), but that increasing device speeds would substantially degrade pedestrian comfort.